Lifestyle Identification and Degree of Risk of Type 2 Diabetes - Izet Bajramovic; Nedzad Imamagic; Edina Djozic; Erol Kovacevic; Amila Hodzic; Ivor Doder; Amel Mekic; Slavenko Likic (Journal of Anthropology of Sport and Physical Education)
The aim of the study was to analyze the relationship between lifestyle level and the risk of type 2 diabetes. The study included 206 respondents who were not diagnosed with diabetes and who were not elite or amateur athletes. The sample was divided into two sub-samples. The first group consisted of respondents aged 18-29 years (n = 104); the second group consisted of respondents aged 30-44 years (n = 102). The FINDRISC questionnaire was used to collect data for the purpose of assessing the risk of type 2 diabetes. The answers to 8 questions provided information about respondent's age, body mass index, waist circumference, physical activity, fruit and vegetable consumption, high-pressure medication, history of hyperglycemia and history of diabetes in the family. The results of the type 2 diabetes risk level indicated the following values: a low level was present in 55%; mild level in 33%; moderate level in 8%; and a high level in 4% of respondents. The results of the study indicated that quality of life decreases with age and the risk of diabetes increases. Therefore, it is important to familiarize people with how to control their weight, their eating habits and their regular physical activity as a preventive method. It is also important to recognize and apply global animation models to maintain and improve the health status of people.